DESIGNING DIRECT REGIONAL HEAD ELECTIONS BY THE GENERAL ELECTION COMMISSION AMIDST THE COVID-19 PANDEMIC - Redi Pirmansyah; Junaidi Junaidi; M. Martindo Merta (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
This study aims to understand the challenges faced in the implementation of direct regional elections by the General Election Commission amid the COVID-19 pandemic in Indonesia in 2020. The research method used is empirical juridical with a field research approach. Data were obtained through interviews with election coordinators and document analysis related to the implementation of elections. The results showed that the implementation of local elections in Indonesia in 2020 faced challenges due to disruptions caused by the COVID-19 pandemic, such as ensuring compliance with health protocols, poor internet quality, violations related to the procurement of Personal Protective Equipment (PPE), public concerns about the spread of COVID-19, disruption of the election process due to delays in resources and infrastructure, and candidate partners (paslon) who often ignore health protocols during their campaigns. Overcoming these challenges requires effective coordination and communication among election coordinators, strict implementation of health protocols, adjustments to schedules, stages, programs, and budgets, and increased community participation. The government also needs to pay attention to the availability of sufficient funds to ensure the smooth implementation of the election.